Multi‐center analysis of practice patterns and outcomes of younger and older patients with mantle cell lymphoma in the rituximab era. Issue 11 (10th August 2021) - Karmali, Reem; Switchenko, Jeffrey M.; Goyal, Subir; Shanmugasundaram, Krithika; Churnetski, Michael C.; Kolla, Bhaskar; Bachanova, Veronika; Gerson, James N.; Barta, Stefan K.; Gordon, Max J.; Danilov, Alexey V.; Grover, Natalie S.; et al.
Abstract: Clinical outcomes and predictors of survival in patients with newly diagnosed mantle cell lymphoma (MCL) treated in the rituximab era (2000–2015) at 12 US academic centers were assessed to identify determinants of survival across age groups. Objectives were to characterize and compare practice patterns, outcomes and prognostic factors for survival in younger patients (age < 65) and older patients (age ≥ 65 years). Among 1162 patients included, 697 were younger and 465 were older. In younger patients, 2‐year progression free survival (PFS) and overall survival (OS) rates were 79% and 92% respectively; blastoid histology, ECOG ≥ 2, and lack of maintenance rituximab (MR) remained statistically relevant to poor OS on univariate analysis (UVA) and multivariate analysis (MVA). In older patients, 2‐year PFS and OS rates were 67% and 86% respectively; lack of maintenance rituximab remained significantly associated with inferior PFS and OS on UVA and MVA ( p  < 0.001). Two‐year PFS rates were 79%, and 67% and 2‐year OS rates were 92% and 86% for ages < 65 and ≥ 65 respectively ( p  < 0.001). First‐line high‐dose cytarabine exposure and/or MR lessened the negative impact of age on survival. Taken collectively, survival outcomes for older patients remain inferior to those of younger patients in the rituximab era. However, maintenance rituximab and potentially high‐dose cytarabine‐based induction can mitigate the negative impact of age on survival.